EFFICACY OF PROPHYLACTIC GENTAMICIN USE IN POSTOPERATIVE URINARY-TRACT INFECTIONS AFTER ENDOSCOPIC PROCEDURES OF THE URINARY-TRACT - (:unkn) unknown (KARGER, 1992)
In this study, the efficacy of prophylactic antibiotic use was investigated. A total of 110 patients undergoing endoscopic procedures of the urinary tract were enrolled in the study. Fifty-five of the patients were treated with 8-hourly, 80 mg gentamicin sulfate of total three doses. The drug administration began just prior to the operation. Seven postoperative infections (12.7%) were detected, the same number as in the control group of 55 patients. The results confirm that there is no place for gentamicin prophylaxis in endoscopic procedures of the urinary tract.
Keywords: GENTAMICIN; ANTIBIOTIC PROPHYLAXIS; ENDOSCOPIC PROCEDURES OF THE URINARY TRACT